Dynamic average modelling of renewable generation sources for real time simulation - Onyinyechi Nzimako (The Journal of Engineering, 2019)
The increase in microgrids and smart grid research comprising renewable generation sources with advanced grid control functionalities is driving the need for sophisticated simulation and hardware in the loop (HIL) test facilities using digital real time simulators (DRTS). Unlike traditional off line simulation tools, DRTS provides fast, continuous real time operation as well as hardware interfaces to test the operation of physical control, protection and power devices before they are installed in the smart/micro grid application. The available computation resources of the DRTS to achieve fast, continuous real time operation impose a limitation on the size and level of detail of the power system model for the simulation and HIL application. Reduced dynamic models that represent the power system and control dynamics with sufficient accuracy provide an acceptable trade-off between the required computation resources and size of the power system model for large simulation applications. This paper discusses the dynamic average modelling of renewable energy generation sources for real time simulation applications.